QOL-08. PHASE II RANDOMIZED STUDY TO EVALUATE EFFICACY AND SATISFACTION OF ROLAPITANT PLUS ONDANSETRON VS. ONDANSETRON MONOTHERAPY IN PREVENTING NAUSEA/VOMITING FOR GLIOMAS RECEIVING RADIATION/TEMOZOLOMIDE. (14th November 2022) - Affronti, Mary Lou; Patel, Mallika; Severance, Erin; Loughlin, Charles; Bradbury, Claire; Herndon, James E; Boyd, Kendra; Lipp, Eric S; Friedman, Henry S; Desjardins, Annick; Johnson, Margaret; Peters, Katherine B
Abstract: BACKGROUND: Nausea and vomiting remain the most feared cancer treatment-related side effects. Trials establishing antiemetic guidelines exclude malignant glioma (MG) patients. In MG patients receiving radiation with concurrent temozolomide, chemoradiation-induced nausea and vomiting (cRINV) rates are 35 and 26%, respectively, which reduce quality of life, treatment adherence, and potentially cancer control.OBJECTIVES: In a randomized phase II open label trial, we compared patient satisfaction and efficacy of ondansetron monotherapy (short-acting 5HT3-RA; 3h half-life) vs. rolapitant (long-acting NK1-RA; 180h half-life) plus ondansetron in preventing cRINV during 6-weeks of daily temozolomide (75 mg/m2/dX42d) with radiation. METHODS: Fifty-three eligible patients receiving chemoradiation were randomized to Arm-A (ondansetron 8mg Days 1-42, rolapitant 180mg on Day 21) or Arm-B (rolapitant on Day 1 plus daily ondansetron). Primary endpoint included the percentage achieving cRINV-complete response (CR; no vomiting or antiemetic rescue) during the first 2-weeks of radiation. Secondary endpoints included cRIN/cRIV rates, preference for rolapitant plus ondansetron, and toxicity. RESULTS: Forty-eight initiated protocol treatment. Mean age=53, 58% male, median KPS 90%, 71% low alcohol N/V risk factor, 73% glioblastoma. During the first 2-weeks of radiation, cRINV-CR was 60% for 25 evaluable patients receiving ondansetron monotherapy and 65% for 23 receiving rolapitant/ondansetron (p< 0.71). Patient-reported cRINV-CR was 61% and 74%, respectively (p< 0.41); cRIN rates (44% Arm-A; 53% Arm-B) were more than cRIV rates (28% Arm-A; 11% Arm-B). More patients receiving ondansetron alone vomited the first 2-weeks (22%) than with rolapitant/ondansetron (0%); p< 0.05. Among 32 patients who completed the study, patients preferred ondansetron (63%) over rolapitant/ondansetron (19%); p< 0.0039; 19% had no preference. Adverse events attributable to antiemetic treatment (fatigue/constipation) were all grade 1-2. CONCLUSIONS: While patients prefer ondansetron monotherapy, there was no difference in cRINV-CR between the first 2-week treatments and some had less vomiting with rolapitant plus ondansetron. We will present overall N/V results.